Advanced automation techniques in adaptive material processing - Chen, XiaoQi, 1963-; Devanathan, R. (Rajagopalan); Fong, Aik Meng (World Scientific, 2002)
This volume presents the editors' research as well as related recent findings on the applications of modern technologies in electrical and electronic engineering to the automation of some of the common manufacturing processes that have traditionally been handled within the mechanical and material engineering disciplines. In particular, the book includes the latest research results achieved through applied research and development projects over the past few years at the Gintic Institute of Manufacturing Technology, Singapore. It discusses advanced automation technologies such as in-process sens.